Predictors of Complete Response and Disease Recurrence Following Chemoradiation for Rectal Cancer - Bitterman, Danielle S.; Resende Salgado, Lucas; Moore, Harvey G.; Sanfilippo, Nicholas J.; Gu, Ping; Hatzaras, Ioannis; Du, Kevin L. (Frontiers in Oncology, 2015)
Objective: Approximately 10-40% of rectal patients have a complete response (CR) to neoadjuvant chemoradiation (CRT), and these patients have improved survival. Thus, non-operative management (“watch-and-wait” approach) may be an option for select patients. We aimed to identify clinical predictors of complete response following CRT. Methods: Patients treated with definitive chemoradiation for T3-T4, locally unresectable T1-T2, low-lying T2, and/or node-positive rectal cancer from August 2004 to February 2015 were retrospectively reviewed. Most patients were treated with 50.4 Gy radiation and concurrent 5-fluoruracil or capecitabine. Patients were considered to have a CR if surgical pathology revealed ypT0N0M0 (operative management), or if they had no evidence of residual disease on clinical and radiographic assessment (non-operative management). Statistical analysis was carried out to determine predictors of CR and long-term outcomes. Results: Complete records were available on 138 patients. The median follow-up was 24.5 mos. 36 patients (26.3%) achieved a CR; 30/123 operatively managed patients (24.5%) and 6/15 (40%) non-operatively managed patients. None of the 10 patients with mucinous adenocarcinoma achieved a CR. CEA ≥5 μg/L at diagnosis (OR 0.190, 95% CI 0.037-0.971, p=0.046), tumor size ≥3 cm (OR 0.123, 95% CI 0.020-0.745, p=0.023), distance of tumor from the anal verge ≥3 cm (OR 0.091, 95% CI 0.013-0.613, p=0.014), clinically node positive disease at diagnosis (OR 0.201, 95% CI 0.045-0.895, p=0.035), and interval from CRT to surgery ≥8 weeks (OR 5.267, 95% CI 1.068-25.961, p=0.041) were independent predictors of CR. The CR group had longer 3-year distant metastasis-free survival (DMFS) (93.7% vs. 63.7%, p=0.016) and 3-year disease-free survival (DFS) (91.1% vs. 67.8%, p=0.038). 3-year locoregional control (LRC) (96.6% vs. 81.3%, p=0.103) and overall survival (OS) (97.2% vs. 87.5%, p=0.125) were higher in the CR group but this did not achieve statistical significance. CR was not an independent predictor of LRC, DMFS, or DFS. Conclusions: CEA at diagnosis, tumor size, tumor distance from the anal verge, node positivity at diagnosis, and interval from CRT to surgery were predictors of CR. These clinical variables may offer insight into patient selection and timing of treatment response evaluation in the watch-and-wait approach.